Human Trafficking as an Economic Crime in Aceh: An Islamic Economic Law Perspective on Qanun Jinayat and Gampong Justice - Marcelia, Ayendri Serley; Rosyid, Maskur (UIN Siber Syekh Nurjati Cirebon, 2025)
Human trafficking constitutes a severe form of economic exploitation and fundamentally contradicts the principles of maqāṣid al-sharī'ah, particularly the preservation of wealth (ḥifẓ al-māl) and life (ḥifẓ al-nafs). This crime harms victims physically and psychologically while undermining their economic rights and disrupting social and economic justice. From the perspective of Islamic economic law, human trafficking is a grave violation of the obligation to uphold economic justice and equitable wealth distribution—core elements of maqāṣid al-sharī'ah. This study aims to analyze and compare the effectiveness of these two legal approaches and to formulate a cooperative and justice-oriented model of resolution. Employing a descriptive qualitative method, data were collected through in-depth interviews, field observations, and document analysis in several regions of Aceh. The findings reveal that the Qanun Jinayat does not explicitly regulate human trafficking offenses, resulting in suboptimal law enforcement. Meanwhile, the Musyawarah Gampong mechanism often fails to ensure adequate protection for victims, creating space for perpetrator impunity. Based on these findings, the study recommends revising the Qanun Jinayat to include specific provisions on human trafficking, enhancing legal training for village authorities, and strengthening legal literacy among the public to bridge the gap between legal norms and social practices. This study positions human trafficking as a violation of the principles of Islamic economic law, which demand distributive justice and the prohibition of exploitation in economic activities. Keywords: human trafficking, Qanun Jinayat, Musyawarah gampong, customary law, justice